Inspiration and Emulation : Selected Studies on Rubens and Rembrandt - Nakamura, Toshiharu (Peter Lang AG International Academic Publishers, 2019)
This book discusses an important theme in art history - artistic emulation that emphasizes the exchange between Flemish and Dutch art in the seventeenth century.